Hardware-and-software diagnostics system for quantitative evaluation of human skin perspiration function - A. M. Vorobei (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Capacitive transducer/adsorption element based hardware-and-software diagnostics system that implements human perspiration measurement and monitoring under normal and pathological conditions (primary hyperhidrosis) was designed.